A5.6 Muscular weakness and pain in patients with rheumatoid arthritis - correlations with electromyography, clinical and serological data. (13th February 2015) - Iorgoveanu, V; Negru, MM; Berghea, F; Deaconu, C; Groseanu, L; Borangiu, A; Opris, D; Ionescu, R
Abstract : Background and objectives: Muscular involvement (mostly by weakness, pain and fatigue) is frequently involved in rheumatological practice. Associated myopathy to rheumatoid arthritis (RA) is an important comorbity that causes supplementary disability. Our objectives are to investigate the muscular involvement in RA with electromyography (amplitude, duration and motor unit potential MUP) and to correlate the data with clinical and laboratory findings. Material and methods: Consecutive patients with RA, weakness and muscle pain were recruited during a 9 month period. Clinical (VAS, muscular testing, 6 min walk test) and laboratory tests (creatinkinase, dehydrogenase lactate, inflammatory markers, vitamin D serological level) were performed. The electromyographic study was pursued with concentric needle for MUP evaluation, then amplitude, duration and polyphasic pattern at deltoid muscle, interosseous, vastus lateralis and anterior tibial muscle were registered. Results: 50 patients (88% women, mean age 62.8 +/-11.5 years) diagnosed with PR and muscle weakness were included. Clinically, DAS 28 (mean 3.76+/-1.44), HAQ (mean 1.49+/-1.12), VAS scale pain (mean 5.18+/-2.5), time up and go test (mean 12.62+/-5.78 min) and 6 min walk test (mean 277.306+/-153.34 metres) were reported. DAS 28 correlates positively with serological levels of creatinkinase (0.768, p < 0.00), C reactive protein (0.421, p < 0.00) and vitamin D level (0.871, p < 0.00) also with polyphasic pattern at deltoid level and duration of MUP in vastus lateralis muscle (0.768, p < 0.00). Polyphasic pattern in the upper limb is related to a similar pattern in lower limb muscles (0.510, p < 0.00). Lower duration of action potential was found in: deltoid (64% of cases), anterior tibial (58%), interosseous (44%) and vastus lateralis muscle (36%). Conclusion: Associated myopathy to RA affects quality of life and function impairment in upper and lower limbs. DAS 28 correlates also with myopathic involvement and vitamin D levels in patients with RA. Most affected muscles are deltoid and anterior tibial muscle. Both upper and lower limbs muscles showed similar polyphasic pattern on electromyography.